A study on the positive and negative effects of different supervisor monitoring in remote workplaces - Li, Shuang; Wang, Yumei (Frontiers in Psychology, 2024)
The current academic research on whether and how the different supervisor monitoring effect in remote workplace is relatively scarce. Based on the Job Requirement Resource (JD-R) Model, this study proposes that as a kind of work resource, interactional monitoring will enhance employees' self-efficacy, further enhance remote employees' work engagement and reduce their deviant behaviors. While as a kind of work requirement, electronic monitoring will decrease employees' self-efficacy, further reduce remote employee's work engagement and increase their deviant behaviors. This study gets the empirical date of 299 employees who experienced remote work. Amos 23.0, SPSS 23.0 software and process plug-in were used to do the hierarchical regression, bootstrap and simple slope analysis, so that to test the hypothesis. This study broadens the research situation and mechanism of different supervisor monitoring, so as to enrich the comprehensive understanding of the effect of them, and also to provide some inspiration and reference for relevant management practices.